METHODS AND TOOLS OF INFORMATION AND TECHNOLOGICAL SUPPORT FOR THE PROCESSES OF FIREARMS TRADE ACCOUNTING - YARIMOVYCH, YURIY; KUNANETS, NATALIIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Biometric scanners are an important element of modern security systems that provide personalized identification of persons who have access to weapons, including sellers, buyers and inspectors. Their use prevents unauthorized access, ensures that the actions of each user are recorded, and increases the level of responsibility for operations with weapons. The most common are fingerprint scanners, which provide quick and accurate identification. Face scanners are also used, which allow contactless recognition of the user, and iris scanners, which are used in conditions of increased security requirements. The article examines modern methods and tools for information and technological support of firearm trade accounting processes, which are a critical component of state control and security. Particular attention is paid to the issues of automation, digital identification, tracking of weapon movement, and ensuring transparency of operations between governmental bodies and private market participants. The potential of implementing blockchain technologies (in particular, Hyperledger Fabric) is analyzed to ensure the reliability and immutability of transactions. The use of graph databases (Neo4j, GraphDB) is considered for modeling complex relationships between accounting entities. Prospects for applying IoT devices, biometric systems, and machine learning methods are outlined to detect anomalies and predict risks. Additionally, the article highlights the use of the Analytic Hierarchy Process (AHP) for formalized decision-making support in selecting technical solutions, assessing risks, and setting development priorities for the information infrastructure under conditions of limited resources.
Keywords: information technologies; weapons accounting; RFID; blockchain; anomalies; intelligent analysis; information security